Antifungal Activities of Natural Products and Their Hybrid Molecules - Vuyolwethu Khwaza; Blessing A. Aderibigbe (MDPI AG, 2023)
The increasing cases of drug resistance and high toxicity associated with the currently used antifungal agents are a worldwide public health concern. There is an urgent need to develop new antifungal drugs with unique target mechanisms. Plant-based compounds, such as carvacrol, eugenol, coumarin, cinnamaldehyde, curcumin, thymol, etc., have been explored for the development of promising antifungal agents due to their diverse biological activities, lack of toxicity, and availability. However, researchers around the world are unable to fully utilize the potential of natural products due to limitations, such as their poor bioavailability and aqueous solubility. The development of hybrid molecules containing natural products is a promising synthetic approach to overcome these limitations and control microbes' capability to develop resistance. Based on the potential advantages of hybrid compounds containing natural products to improve antifungal activity, there have been different reported synthesized hybrid compounds. This paper reviews different literature to report the potential antifungal activities of hybrid compounds containing natural products.